31odernisasi Hukum di Indonesia Adakah -Peran Golongan Borjuis Seperti Di Eropa Barat ?- - Muhammad Syamsudin (Jurnal Hukum IUS QUIA IUSTUM, 2006)
The Modernization of law in West Europe, in the process of the modernization was supported by the bourgeois liberal capitalism group. The group was able to changefundamentally the social, cultural political and economic aspects of the EuropeanCommunity who has already established the modem concept of law. Is the condition alsooccured in Indonesia?